Pendekatan Lean Manufacturing Untuk Meminimasi Waste Produksi UMKM Swadi Cipta Karya - Wahyudi, Rizqi; Nugraha, Andhyka Tyaz; Anam, Khoirul (Faculty of Industrial Technology Universitas Islam Indonesia, 2024)
Waste is a problem whose existence needs to be minimized, because waste can affect the productivity of a business. This research was conducted at UMKM Swadi Cipta Karya which operates in the convection sector with the main product being fishing bags. The main objective of this research is to minimize waste that occurs in the fishing bag production process. This research uses a lean manufacturing approach with several analysis stages in it, such as value stream mapping (VSM), waste failure mode effect analysis (WFMEA), value stream analysis tools (VALSAT), fishbone diagram, and kaizen. Data in the research were obtained through direct observation by identifying and measuring the time of activities carried out in the fishing bag production process. The results of the analysis using WFMEA conclude that there are main types of waste in the production process, namely transportation, unnecessary motion, and waiting. Analysis of tool selection using VALSAT concluded that PAM was selected to be used to eliminate waste, activities that had to be minimized were more dominant than activities that had to be eliminated (eliminated). These results also provide a layout design that can be implemented by MSMEs. Analysis using Kaizen concludes that the results of 5S are designing the layout well, arranging materials, conducting training, preparing materials, and placing sewing results in baskets to minimize or eliminate waste.